A systematic approach to testing educational activity of students - Chepurko, I. P. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses the use of a systematic approach to testing educational activity of students as one of the methods of control in high school. In recent years, testing a promising way to measure the success and quality of students' knowledge is becoming more and more widespread and relevance. On the basis of studies of leading Ukrainian scientists proved that the testing - a multidimensional concept, which should be considered from different points of view. It is important to take into account the advantages and disadvantages of testing, based on the principles of the test control. This systematic approach can cover a variety of testing components, present it as a systemic phenomenon in the educational process of the university. In developing the test to be considered components of the test system, such as the purpose of the test control, the contents of the test tasks, kinds and forms of tests of the controls and the like. That is, consider testing the educational activities of students with systematic approach.